Elevated incidence of fractures in women with invasive breast cancer. Issue 2 (February 2016) - Edwards, B.; Gradishar, W.; Smith, M.; Pacheco, J.; Holbrook, J.; McKoy, J.; Nardone, B.; Tica, S.; Godinez-Puig, V.; Rademaker, A.; Helenowski, I.; Bunta, A.; et al.
Abstract Summary This study evaluates the incidence of bone fractures in women with BC.We found that women with invasive breast cancer are at an increased risk for bone fractures, with fractures most commonly occurring at lower extremity and vertebral sites. The risk is further increased in women undergoing cancer therapy. Introduction Bone loss and fractures in breast cancer have generally been attributed to aromatase inhibitor use. This study assessed the incidence of fractures after invasive breast cancer diagnosis and evaluated bone density and FRAX risk calculation at time of fracture occurrence. Methods Retrospective cohort study of women with invasive breast cancer [June 2003–December 2011] who participated in an academic hospital based genetic biobank. Demographic and clinical characteristics were abstracted from the electronic medical record (EMR). Results A total of 422 women with invasive breast cancer were assessed; 79 (28 %) sustained fractures during the observation period; fractures occurred at multiple skeletal sites in 27 cases (116 fractures). The incidence of fractures was 40 per 1000 person-years. Women who sustained fractures were mostly white and had a family history of osteoporosis (36.9 %, p  = 0.03) or history of a prior fracture (6/79, p  = 0.004). Fractures occurred 4.0 years (range 0–12 years) after cancer diagnosis. Fracture cases had femoral neck bone mineral density (BMD) of 0.72 + 0.12 g/cm2, T-score of −1.2, that is, within the low bone mass range. Fractures most commonly occurred in lower extremities, vertebral, and wrist sites. Hip fractures accounted for 11 % of fractures, occurring at a median age of 61 years. Conclusions Fractures occur shortly after commencing cancer therapy. Rapid bone loss associated with cancer therapy may precipitate fractures. Fractures occur at relatively higher BMD in BC. Occurrence of fractures in invasive breast cancer raises the possibility of cancer-induced impairment in bone quality.